The Influence of Customer Experience on Interest in Purchasing Game Items on Mobile Legends Mediated by User Game Engagement - Saputra, Dimas Candra; Parwati, Kardina Yudha (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
Increasing competition in the mobile gaming industry requires companies to continue innovating in order to maintain user interest. Mobile Legends, as one of the most popular games, faces the challenge of declining revenue and user numbers, indicating the need for a new approach to increasing in-game item purchases. This study aims to investigate the influence of customer experience on the intention to purchase game items in Mobile Legends, mediated by user game engagement. The research method used is quantitative with an explanatory approach. This study employs a sample of 210 respondents through an online questionnaire distribution. Respondents were Mobile Legends users in Indonesia who had played the game within the past six months and were at least 18 years old. Data analysis in this study used Partial Least Square (PLS) with the SmartPLS 4.1 programme. The results showed that customer experience had a positive and significant effect on the interest in purchasing game items and on user game engagement. Additionally, user engagement also has a positive and significant effect on the intention to purchase game items. These findings indicate that user engagement acts as a partial mediator in the relationship between customer experience and the intention to purchase game items. The managerial implications of this study highlight the importance of enhancing user experience and engagement within the game to drive the intention to purchase game items.